PROFESSİONAL DEVELOPMENT: INTERNATİONAL QUALİFİCATİONS AND CERTİFİCATES FOR ENGLİSH TEACHERS - Jo'rayeva Laylo Sirojiddin qizi; XATIRA GAYBULLAYEVA (NAZARIY VA AMALIY FANLARDAGI USTUVOR ISLOHOTLAR VA ZAMONAVIY TA’LIMNING INNOVATSION YO’NALISHLARI, 2026)
This paper explores the importance of professional development for English language teachers through internationally recognized qualifications and certificates. As global demand for high-quality English education continues to rise, teachers are expected to demonstrate both strong language proficiency and advanced pedagogical skills. International certifications such as TESOL, TEFL, CELTA, and DELTA serve as reliable indicators of a teacher’s competence, providing structured training in methodology, classroom management, and assessment. These qualifications not only enhance teaching effectiveness but also open opportunities for career advancement in international schools, language centers, and online learning platforms. The study emphasizes that obtaining global teaching credentials empowers educators to meet international standards, adapt to diverse learning environments, and contribute to improved learning outcomes. Professional development through such certifications is therefore essential for teachers seeking long-term growth and global employability.